BEDDING QUALITY ON CONVENTIONAL AND TUNNEL VENTILATION BROILER’S HOUSING - NÄÄS, IRENILZA ALENCAR; MIRAGLIOTTA, MIWA Y.; BARACHO, MARTA S.; MOURA, DANIELLA J.; SALGADO, DOUGLAS D. (Revista Brasileira de Engenharia de Biossistemas, 2007)
Bedding quality is responsible for the increase of gases production inside poultry housing. Both concentration and emission potential of those gases are related to items such as humidity and pH, which are product of the housing environmental conditions. The main objective of this research was to evaluate the bedding conditions as function of adopted poultry rearing environment:conventional and tunnel type, with distinct ventilation and broiler density. The housing with higherstocking density presented higher litter humidity values and pH. In the housing central region the lowest litter humidity value was found. During summer bedding humidity values were higher than during the winter; and higher in the housing with the higher stocking density. As ammonia emissionis related to both litter humidity and pH, and those are linked to the housing environmental conditions, there is a need to find the balance between ideal rearing and ventilation conditions for broilerproduction sustainability under tropical climate.